The SEM & AFM images of MEH-PPV films below CLA region - Nurjuliana, Juhari; Wan Haliza, Abd Majid, Prof. Dr.; A. I., Zainol (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/